2019
DOI: 10.1103/physrevb.100.220407
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced magnetic transition and spin fluctuations in the quantum spin-liquid candidate CsYbSe2

Abstract: Two-dimensional triangular-lattice materials with spin-1/2 are perfect platforms for investigating quantum frustrated physics with spin fluctuations. Here we report the structure, magnetization, heat capacity and inelastic neutron scattering (INS) results on cesium ytterbium diselenide, CsYbSe2. There is no long-range magnetic order down to 0.4 K at zero field. The temperature dependent magnetization, M (T ), reveals an easy-plane magnetic anisotropy. A maximum is found in M (T ) around T ∼1.5 K when magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 61 publications
2
68
0
Order By: Relevance
“…These results are consistent with the inductively-coupled plasma measurements of chemical composition of the sample (see method for details). Although Yb ions in the Na layers may be magnetic, our frequency-dependent ac susceptibility measurements down to 90 mK can be well described is centered around the K point, consistent with the previous work [32], and decreases significantly with increasing temperature.…”
supporting
confidence: 91%
“…These results are consistent with the inductively-coupled plasma measurements of chemical composition of the sample (see method for details). Although Yb ions in the Na layers may be magnetic, our frequency-dependent ac susceptibility measurements down to 90 mK can be well described is centered around the K point, consistent with the previous work [32], and decreases significantly with increasing temperature.…”
supporting
confidence: 91%
“…This UUD phase exhibits a magnetization plateau with 1/3 saturated moment ( M s ). Recently, even in QSL candidates A Yb Ch 2 ( A = Na and Cs, Ch = O, S, Se), one TAF family with effective spin-1/2 Yb 3+ ions and easy-plane anisotropy, the UUD phase has been proposed under applied fields 55 58 . Experimentally, more complex QSSTs have been observed for Ba 3 CoSb 2 O 9 59 65 .…”
Section: Resultsmentioning
confidence: 99%
“…One example is Ba 3 CoSb 2 O 9 , another TAF with effective spin-1/2 Co 2+ ions, which orders around 3.5 K and exhibits a UUD phase at ultralow temperatures [32][33][34] . More recently, the UUD phase also has been proposed for AYbCh 2 (A = Na and Cs, Ch = O, S, Se), one TAF family with effective spin-1/2 Yb 3+ ions [35][36][37][38] . Further detailed experimental and theoretical studies on Ba 3 CoSb 2 O 9 revealed more complex quantum spin state transitions (QSSTs) [39][40][41][42][43][44][45] .…”
mentioning
confidence: 99%